Alcohol Septal Ablation or Septal Myectomy? An Updated Systematic Review and Meta-Analysis of Septal Reduction Therapy for Hypertrophic Obstructive Cardiomyopathy - Zheng, Xifeng; Yang, Bin; Hui, Haosheng; Lu, Bing; Feng, Yinhui (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate the safety and effectiveness of alcohol septal ablation (ASA) and septal myectomy (SM) for the treatment of hypertrophic obstructive cardiomyopathy. Methods: We searched the PubMed, MEDLINE, EMBASE, and CBM databases for observational research articles related to ASA and SM published from the establishment of the databases to November 2021. Manual searching was performed as a supplementation, and all selected articles were highly related to our target. RevMan5.3 software was employed for the meta-analysis. Results: A totally of 3647 cases (1555 cases treated with ASA and 2092 cases treated with SM) were included. The results of the systematic review indicated no statistically significant difference (relative risk ratio = 0.95; 95% confidence interval: 0.65-1.40; P = 0.80) in postoperative all-cause mortality between patients treated with ASA and SM, but both the reduction in the postoperative left ventricular outflow pressure difference (Weighted mean difference = 12.29; 95% confidence interval: 6.06, 18.52; P = 0.0001) and the improvement of cardiac function (Weighted mean difference = 0.31; 95% confidence interval: 0.16, 0.45; P < 0.0001) in the AS group were slightly inferior to those in the SM group, in addition to a higher risk of pacemaker implantation (relative risk ratio = 2.83; 95% confidence interval: 2.06, 3.88; P < 0.00001). Conclusion: Both ASA and SM have a high degree of safety, but the reduction in the postoperative left ventricular outflow pressure difference and the improvement in cardiac function are slightly inferior to SM. The operative plan should be chosen through multidisciplinary discussions in combination with the wishes of the patients and the actual clinical situation.